A prospective observational study on efficacy of modified rheumatoid arthritis protocol of rituximab (2000 mg) on patients of pemphigus - Singh, Santosh Kumar; Satyaraj, Prannav; Sachan, Prasoon (International Journal of Research in Dermatology, 2021)
Background: Rituximab (RTX), an anticluster of differentiation 20 antibody, targets B lymphocytes, has been shown in open series studies to be effective in treating pemphigus. The objective was to evaluate whether a modified rheumatoid arthritis protocol, in which the patient received four doses of 500 mg of rituximab at an interval of two weeks was safe and effective in pemphigus management. Methods: It was a prospective observational study in which 46 pemphigus patients included and four doses of 500 mg of RTX at an interval of two weeks given and number of doses required for complete remission (CR), proportion of patient respond partially or doesn’t respond or relapsed after CR. Results: We enrolled 46 patients in the study, 8 with pemphigus foliaceus (PF) and 38 with pemphigus vulgaris (PV). 20 were male and 26 were female followed up for 15±4.24 months (12-18). All patient responded to therapy. CR of 23 patient after 2 dose OF 500 mg RTX ,of 18 patient after 3 dose, 5 patient partial remission (PR) after 4 doses. All patient were on 100 mg OD azathioprine. PR, all have oral lesions got CR after 3 weeks of 4th dose. 3 patients relapsed MD 11±2.8 months (9-13 months) and given additional dose of 500 mg RTX and got resolved in 3 weeks. Conclusions: We found modified rheumatic arthritis protocol for RTX was shown to be effective in treatment of pemphigus patient and relapse cases with additional dose. Immunological assay were not performed to limit the study.